Tempat Kerjaku Menyenangkan: Adaptasi Skala Workplace Fun dalam versi Bahasa Indonesia - Abid, Luthfi Naufal; Kadiyono, Anissa Lestari (Universitas Batanghari Jambi, 2025)
The purpose of this study is to adapt the workplace fun scale into the Indonesian version of the scale. This study is based on the ITC (International Test Commission) guidelines for the adaptation process and conducts statistical analysis with the Cronbach's Alpha reliability test and Confirmatory Factor Analysis (CFA). CFA results This implies that the model proposed in this study is valid for assessing Workplace Fun in Indonesia and can be used for future research on Workplace Fun in Indonesia.